Cowboy country - Scott, Ann Herbert; Lewin, Ted (New York : Clarion Books, 1993)
An "old buckaroo" tells how he became a cowboy, what the work was like in the past, and how this life has changed.
Keywords: Cowboys -- West (U.S.) -- Juvenile literature; Cowboys; West (U.S.) -- Social life and customs -- Juvenile literature; West (U.S.) -- Social life and customs